Inadequate Triglyceride Management Worsens the Durability of Dipeptidyl Peptidase-4 Inhibitor in Subjects with Type 2 Diabetes Mellitus - Masashi Shimoda; Maiko Miyoshi-Takai; Shintaro Irie; Akihito Tanabe; Atsushi Obata; Seizo Okauchi; Hidenori Hirukawa; Tomohiko Kimura; Kenji Kohara; Shinji Kamei; Tomoatsu Mune; Kohei Kaku; et al. (Journal of Diabetes Research)
Dipeptidyl peptidase-4 (DPP-4) inhibitors are often used all over the world and exert various beneficial effects including glucose-lowering effect in many subjects with type 2 diabetes. It is poorly understood, however, which factors are closely related with the durability of glucose-lowering effect by DPP-4 inhibitor. In this study, we examined retrospectively which factors could mainly influence the durability of DPP-4 inhibitor. We enrolled 212 participants with type 2 diabetes to whom DPP-4 inhibitor was administered for over 1 year without an addition or increase of other hypoglycemic agents. Age and baseline HbA1c level were significantly higher in the effective group than those in the ineffective group. The effective group had a tendency of smaller amounts of weight change, average total cholesterol, and average triglyceride compared with the ineffective group. Multiple logistic regression analysis showed that average triglyceride and baseline HbA1c were independent predictors associated with the durability of DPP-4 inhibitor. Moreover, an average triglyceride level contributed to the durability of DPP-4 inhibitor in the obese group (BMI ≥ 25 kg/m2) but not in the nonobese group (BMI < 25 kg/m2). These results suggest the importance of strict triglyceride management to maintain the durability of glucose-lowering effect by DPP-4 inhibitor, especially in obese subjects with type 2 diabetes.